Jel' jasno, prijatelju? . Is It Clear, My Friend? - Aćimović, Dejan (DA Film Croatia ; Gama Studio, 2000)
This prison action movie is colloquially referred to as the first film of Croatia’s Serbian minority on account of its director and the first post-1991 appearance of one-time house actor Rade Šerbedžija in a Croatian film. Set in the 1980s and supposedly based on a true story, the film unsuccessfully tries to use life behind prison bars as a sort of metaphor for the overall abuses of the Yugoslav communist regime. The film’s central character is quiet accountant Martin who is wrongly convicted of murder and sentenced to twelve years in a high-security, communist style prison in Stara Gradiška. All kinds of criminals live in this institution – from plain murderers and rapists to political prisoners and psychopaths. In spite of restrictions, inmates gamble, try to evade their duties and plan to escape. Martin soon discovers that the guards are as much a threat to his safety as the other inmates as he witnesses brutal violence, torture, sexual assault, and cold-blooded murder on a daily basis. Similar events cause a prison riot and Martin is involved as one of its leaders. A special agent is called from Belgrade to solve the problem. Seemingly friendly at first, he eventually betrays the rebellious prisoners and order is reestablished with many of the prisoners killed.